Bacteriological Quality of Farmed Freshwater Fish and Shellfish Meant for Export - J.R., Bandekar; A.S., Kamat; M., Karani; V., Dhokane; R., Shashidhar; A., Kakatkar; N., Ghadge; A., Bhat; V., Venugopal; S.B., Warrier (Fishery Technology, 2025)
Bacteriological screening of 48 samples comprising of 12 samples of headless and 6 samples of whole prawn (Macrobrachium rosenbergii), 24 samples of processed rohu and 6 samples of whole rohu (Labeo rohita) obtained from fish processing factories of Kakinada and Mumbai were screened for aerobic plate count (APC) and for pathogens including Salmonella sp., Vibrio cholerae, Escherichia coli, Staphylococcus aureus and Listeria monocytogenes. The samples of processed rohu (steak) obtained in four different batches (18, samples) were of good bacteriological quality. The APC was 20 cfu/g). However, no other pathogens were detected in any of the samples. APC was > 105 cfu/g in 33% of whole rohu samples obtained from Kakinada. Â£. coli (<20 cfu/g) was detected in 80% of the samples. However, all the samples were free from Salmonella, V. cholerae, S. aureus and L monocytogenes. APC was found to be greater than 106 cfu/g in 33% samples of whole prawn; however, APC in headless prawn was <106 cfu/g. Salmonella contamination was found in 33% samples of whole and 42% samples of headless prawn when tested biochemically. However, serological testing of the presumptive positive isolates showed that whole prawn samples were free from Salmonella but 42% samples of headless prawn were positive and serotypes were S. typhimurium and S. worthington. E. coli was detected in 50% the samples of whole prawn, and 25% of the samples of headless prawn (<20 cfu/g). All the samples were free from V. cholerae, S. aureus and L. monocytogenes. The results suggested the need for implementation of good hygienic practices including HACCP and GMP for the improvement of microbial quality of aquacultured fishery products to meet international quality standards.